Rocket Measurements of Electron Energy Spectra From Earth's Photoelectron Production Layer. Issue 17 (31st August 2022) - Collinson, Glyn A.; Glocer, Alex; Chornay, Dennis; Michell, Robert; Pfaff, Rob; Cameron, Tim; Uribe, Paulo; Frahm, Rudy A.; Rosnack, Traci; Pirner, Chris; Gass, Ted; Clemmons, Jim; et al.
Abstract: Photoelectrons are crucial to atmospheric physics. They heat the atmosphere, strengthen planetary ambipolar electric fields, and enhance the outflow of ions to space. However, there exist only a handful of measurements of their energy spectrum near the peak of photoproduction. We present calibrated energy spectra of pristine photoelectrons at their source by a prototype Dual Electrostatic Analyzer (DESA) instrument flown on 11 July 2021 aboard the Dynamo‐2 sounding rocket (NASA № 36.357). Photopeaks arising from 30.4 nm He‐II spectral line were observed throughout the flight above 120 km. DESA also successfully resolved the rarely observed N2 absorption feature. Below 10 eV observations were in good agreement with the GLOW suprathermal electron. Above 10 eV fluxes substantially deviated from the model by as much as an order of magnitude. Plain Language Summary: We designed, built, and flew a new scientific instrument for the measurement of photoelectrons which are created when sunlight shines on the upper atmosphere. The instrument was launched on a suborbital rocket from NASA Wallops Flight Facility just before 2 p.m. on 11 July 2021. The rocket flew to an altitude of 131 km before splashing down in the Atlantic Ocean 8 min later. The instrument gathered scientific data during the flight, measuring the energy spectrum of electrons in Earth's ionosphere. Historical observations of electron spectra at these altitudes are extremely rare, and are often uncalibrated and/or not archived. We present calibrated observations of the pristine spectra of Earth's electrons near their source as a reference for future computer modeling and exploration of Earth's ionosphere. Key Points: We present in situ observations from a plasma spectrometer flown on a rocket to 131 km in the daytime mid‐latitude ionosphere The instrument returned calibrated measurements of the energy spectra of pristine photoelectrons near the peak of production The N2 absorption feature and He‐II photopeaks were partially resolved. Observations are compared with the GLOW electron model